The lives of women in a land reclamation project: gender, class, culture and place in Egyptian land and water management. Issue 1 (April 2019) - Rap, Edwin; Jaskolski, Martina
This article links feminist political ecology with the academic debate about commoning by focusing on the gendered distribution of common pool resources, in particular land and water. The research is set in the context of a coastal land reclamation project in Egypt's Nile Delta, in a region where conflicts over resources such as arable land and fresh water are intensifying. Drawing on recent literature on commoning, we analyse the conditions under which different groups of resource users are constrained or enabled to act together. The article presents three case studies of women who represent different groups using land and water resources along the same irrigation canal. Through the concepts of intersectionality, performativity, and gendered subjectivity, this article explores how these women negotiate access to land and water resources to sustain viable livelihoods. The case studies unpack how the intersection of gender, class, culture, and place produces gendered subject positions in everyday resource access, and how this intersectionality either facilitates or constrains commoning. We argue that commoning practices are culturally and spatially specific and shaped by pre-existing resource access. Such access is often unequally structured along categories of class and gender in land reclamation and irrigation projects.